Establishment and application of a rapid diagnostic method for BVDV and IBRV using recombinase polymerase amplification-lateral flow device - Wang, Yan; Shang, Jinyuan; Li, Zhijie; Zhang, Ao; Cheng, Yuening (Frontiers in Veterinary Science, 2024)
Bovine Viral Diarrhea Virus (BVDV) and Infectious Bovine Rhinotracheitis Virus (IBRV) are the two most prevalent infectious diseases in cattle. They both can cause persistent infection and immunosuppression, resulting in significant economic losses in the livestock industry. Therefore, rapid detection of early BVDV and IBRV infections is crucial. In this study, a method for the rapid detection of BVDV and IBRV was established by using recombinase polymerase amplification (RPA) combined with lateral flow device (LFD). By optimizing the temperature and time conditions of the RPA reaction, the sensitivity, specificity, and clinical performance were evaluated. The results indicated that the RPA reaction could be completed at 40°C within 25 min. The LOD for BVDV and IBRV by RPA-LFD were 5.1 × 101 copies/μL and 6.65 × 101 copies/μL, respectively, with no cross-reactivity observed with other viruses such as CSFV, BRSV, BPIV3, BRV, and BCoV. Testing of 32 clinical samples showed consistent results between RPA-LFD and qPCR. The RPA-LFD method established in this study can be used for the rapid clinical detection of BVDV and IBRV, which providing a rapid and convenient molecular biology approach for on-site rapid detection and epidemiological investigations. Simultaneously, it offers technical support for the prevention and control of these viruses.